Reshaping Ullmann Amine Synthesis in Deep Eutectic Solvents: A Mild Approach for Cu-Catalyzed C–N Coupling Reactions With No Additional Ligands - Quivelli, Andrea Francesca; Vitale, Paola; Perna, Filippo Maria; Capriati, Vito (Frontiers in Chemistry, 2019)
The CuI-catalyzed Ullmann amine cross-coupling between (hetero)aryl halides (Br, I) and aromatic and aliphatic amines has been accomplished in deep eutectic solvents as environmentally benign and recycling reaction media. Under optimized conditions, the reaction proceeds smoothly under mild conditions (60–100°C) in air, in the absence of ligands, with a catalyst (CuI) loading of 10 mol% and K2CO3 (aliphatic primary and secondary amines) or t-BuOK (aromatic amines) as the base. A variety of amines have been synthesized in yields up to 98% with a broad substrate scope.